International marketing - Cateora, Philip R. (Mc Graw Hill Irwin, 2002)
Cateora and Graham's "International Marketing" is far and away the best selling text in the field, with a pioneering approach to making the material accessible and relevant that has become the standard by which other books are judged. Providing a well-rounded perspective of international markets that encompasses history, geography, language, and religion as well as economics, Cateora helps students to see the cultural and environmental uniqueness of any nation or region. The 13th edition reflects all the important events and innovations to affect global business within recent years, while including several new and updated technological learning tools.